Reduction of mycotoxin citrinin in Monascal Broken Rice (MBR) via exogenous tannic acid supplementation and chemometric analysis (Asian Journal of Agriculture, 2024)
Abstract. Phanumong P, Srisuvor N, Sarawong C, Norajit K, Wattanakul J, Kumtabtim U, Nuclear P, Kraboun K. 2024. Reduction of mycotoxin citrinin in Monascal Broken Rice (MBR) via exogenous tannic acid supplementation and chemometric analysis. Asian J Agric 8: 153-160. Addressing the presence of mycotoxin citrinin in Monascal Broken Rice (MBR) is crucial. Incorporating Exogenous Tannic Acid (ETA) into Monascus substrate effectively diminished citrinin accumulation in angkak. This research explored the impact of 10-20 mg/mL ETA supplementation on reducing citrinin levels in MBR and altering its pigments, glucosamine, monacolin K, fatty acids, and antioxidant properties. The relationship among these factors in MBR was examined using Principal Component Analysis (PCA). ETA supplementation markedly decreased citrinin levels in MBR by over 73.26% compared to the control group while enhancing pigments, glucosamine, monacolin K, fatty acid content, as well as catalase (CAT), superoxide dismutase (SOD), superoxide anion (?O-2), and hydroxyl free radical (HO•) scavenging capabilities. The M. purpureus generated higher contents of unsaturated fatty acids in ETA treatments, such as linoleic acid (C18:2) at 30-32%, followed by oleic acid (C18:1) ranging from 23 to 24%, compared to the control (no ETA), 25.09% for C18:2 and 20.23% for C18:1. The association among oleic acid, linoleic acid, linolenic acid, and citrinin content was evident through PCA loading plots and Pearson's correlation coefficient. ETA supplementation is a viable approach to reduce citrinin concentration in MBR. Applying multivariate analysis, PCA, and Pearson's correlation coefficient provided a comprehensive understanding of the interrelation among various factors in MBR after ETA treatment.
Keywords: Angkak, exogenous tannic acid, monascal broken rice, Monascus purpureus, mycotoxin citrinin